Public Restrooms in Neighborhoods and Public Spaces: a Qualitative Study of Transgender and Nonbinary Adults in New York City - Liadh Timmins (Sexuality Research and Social Policy, 2021)
Introduction: The purpose of this study is to qualitatively explore transgender and nonbinary (TGNB) individuals’ experiences with bathroom use in neighborhoods and public spaces in the context of navigating experiences of harassment, lack of safety, and discrimination in New York City. Methods: Forty diverse TGNB individuals were recruited in the summer of 2017 in New York City for semi-structured qualitative interviews on health and neighborhoods. Inductive thematic analysis coding process was used to determine themes. Themes related to public bathroom use were compiled and analyzed. Results: A total of 31 participant interviews identified bathroom use as an experience that shapes their health and wellbeing. Major themes included avoiding restroom use or planning travel around perceived bathroom access; planning bathroom use compromised mental health and self-image; delaying bathroom use to avoid harassment that leads to negative physical health effects; perceived gender presentation limited bathroom use; and bathrooms advertised as gender-neutral promoted safety and comfort. Conclusions: In a diverse, urban sample of TGNB individuals, bathroom use was identified as relevant to physical and mental health. Despite progressive bathroom laws in the state and city in which the study was conducted, respondents described how bathroom use influences how they move throughout their day. We demonstrate the continued importance of nondiscriminatory access to public spaces such as restrooms to the health of TGNB populations and the need for further prospective research elucidating the impact of nondiscrimination legislation.